Indian Horror: The Western monstrosity and the fears of the nation in the Ramsay Brothers’ Bandh Darwaza - Valančiūnas, Deimantas (Acta Orientalia Vilnensia, 2011)
Vilnius UniversityThis paper investigates Indian horror films as a site of socio-economical tensions in India at the end of the 1980s through the employment of the postcolonial reading of the 1990 Ramsay brothers’ horror film Bandh Darwaza. This paper argues that specific references to the European gothic tradition and employment of imagery and interpretation of a western monstrosity (Dracula) in the film are not merely the exploitation of the exotic discourse, but an unconscious articulation of fears and anxieties summoned by the specific socio-economic conditions of India. The political turmoil and the economic changes at the end of the 1980s created a specific platform for fears and anxieties that were articulated through the deformed monsters of the western gothic tradition.